ANALYSIS OF POVERTY DETERMINANTS AFTER FISCAL DECENTRALIZATION IN EASTERN INDONESIA - Rebecca Cindy Sartika; Cahyaning Budi Utami; Ivana Rosediana Dewi (EP FEB UNS, 2025)
Fiscal decentralization in Indonesia has been actively implemented since January 1, 2001, with the expectation that regions can better utilize their economic potential to accelerate community welfare, particularly in reducing poverty in Eastern Indonesia. This study investigates the effects of Regional Economic Growth (LNPDRB), Human Development Index (IPM), Labor Force Participation Rate (TPAK), Regional Native Income Growth (LNPAD), and Capital Expenditure Growth (LNBM) on the percentage of poor people (PPMISKIN) across 16 provinces in Eastern Indonesia during the 2012–2017 period. Using descriptive statistics and panel data estimation with the Fixed Effect Model (FEM) and cross-section SUR in Eviews 10, this quantitative study provides empirical evidence on the determinants of poverty reduction. The results indicate that IPM significantly reduces PPMISKIN (β = –0.2462; p = 0.0000), while TPAK has a negative effect (β = –0.0379; p = 0.0623). LNPAD also significantly decreases PPMISKIN (β = –1.4014; p = 0.0001). Conversely, LNBM has a positive and significant effect on PPMISKIN (β = 0.4619; p = 0.0132). Meanwhile, LNPDRB is statistically insignificant in reducing poverty (β = 0.0181; p = 0.3142). These findings underscore the greater influence of human development, labor participation, and regional fiscal capacity compared to economic growth in alleviating poverty in Eastern Indonesia.